Analysis Of Iron And Vitamin C Levels In "Guchiro" As An Altenative Food To Prevent Anemia In Pregnant Women (JURNAL PROTEKSI KESEHATAN, 2023)
According to the World Health Organization (WHO), around 35-37% of pregnant women experience iron deficiency and this increases with gestational age. Based on the results of research by Indonesian Ministry of Health, it is known that 48.9% of pregnant women in Indonesia experience anemia. Researchers are interested in making an innovative product of sago mochi with rosella (Hibiscus sabdariffa L.) flower jam as a non-pharmacological alternative to prevent anemia. The aim of this research is to analyze the levels of iron and vitamin C in "GUCHIRO" as a food to prevent anemia in pregnant women. This research was carried out from January 2023 to October 2023 at the integrated laboratory of the Riau Ministry of Health Polytechnic and the Pekanbaru BPPSI Laboratory. The sample in this research is the sample used is food made from processed sago and rosella flowers. To determine iron levels using the Atomic Absorption Spectrophotometry (SSA) method and vitamin C levels using the Absorption Spectrophotometry method which was carried out at the Center for Product Development and Industrial Standardization (BPPSI) in Pekanbaru city. The results of laboratory tests on Guchiro samples showed that Guchiro's iron levels were 88.5404 and vitamin C levels were 2.82%.